2009
DOI: 10.1080/13811110903266418
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-10 −1082, IFN-γ +874, and TNF-α −308 Genes Polymorphisms in Suicidal Behavior

Abstract: In this study, it was determined whether the IL-10 -1082, IFN-gamma +874, and TNF-alpha -308 polymorphisms were associated with suicidal behavior. One hundred forty five patients with suicidal behavior and 160 normal individuals were genotyped for IL-10 -1082, IFN-gamma +874, and TNF-alpha -308 polymorphisms using ASO-PCR method. TNF-alpha -308 G/G genotype has been increased in males with completed suicide behavior versus control group (p value = 0.017). IL-10 -1082 A/A genotype is higher in both male and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…Studies of relationships between functional polymorphisms in cytokine genes and suicide attempts are few and do not provide a consensus. Investigations of the functional polymorphism TNF-α -308 (A/G) variously have found no differences in suicide attempters with various psychiatric diagnosis ( n =193) vs. healthy controls ( n =420) (Sáiz et al, 2008); a positive association between the GG genotype and depressed suicide attempters ( n =204) vs. depressed non-attempters ( n =97); and (in a sample with both sexes) greater prevalence in male suicides ( n =28) than in non-psychiatric controls ( n =46) (Omrani et al, 2009). Similarly, one study (Lee and Kim, 2010) of TGF-β1 functional polymorphisms found no differences in either codon 10 or codon 20 polymorphisms in depressed suicide attempters ( n =124) compared with depressed non-attempters ( n =61) or healthy controls ( n =125), whereas another study (Omrani et al, 2012) found the TGF-β1-10 polymorphism to be more prevalent in suicide completers ( n =145) compared to non-psychiatric controls ( n =200).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of relationships between functional polymorphisms in cytokine genes and suicide attempts are few and do not provide a consensus. Investigations of the functional polymorphism TNF-α -308 (A/G) variously have found no differences in suicide attempters with various psychiatric diagnosis ( n =193) vs. healthy controls ( n =420) (Sáiz et al, 2008); a positive association between the GG genotype and depressed suicide attempters ( n =204) vs. depressed non-attempters ( n =97); and (in a sample with both sexes) greater prevalence in male suicides ( n =28) than in non-psychiatric controls ( n =46) (Omrani et al, 2009). Similarly, one study (Lee and Kim, 2010) of TGF-β1 functional polymorphisms found no differences in either codon 10 or codon 20 polymorphisms in depressed suicide attempters ( n =124) compared with depressed non-attempters ( n =61) or healthy controls ( n =125), whereas another study (Omrani et al, 2012) found the TGF-β1-10 polymorphism to be more prevalent in suicide completers ( n =145) compared to non-psychiatric controls ( n =200).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, one study (Lee and Kim, 2010) of TGF-β1 functional polymorphisms found no differences in either codon 10 or codon 20 polymorphisms in depressed suicide attempters ( n =124) compared with depressed non-attempters ( n =61) or healthy controls ( n =125), whereas another study (Omrani et al, 2012) found the TGF-β1-10 polymorphism to be more prevalent in suicide completers ( n =145) compared to non-psychiatric controls ( n =200). Single reports found the IL-10 -1082 genotype higher in suicides than non-psychiatric controls and the IFN-γ + 874 genotype more prevalent in male suicides (Omrani et al, 2009), and no differences in polymorphisms of the IL-1 gene complex [ IL-1α -889 C/T, IL-1β + 3953 C/T, IL-1RA (86 bp) n ] between a mixed diagnostic group of suicide attempters ( n =193) and healthy controls ( n =420) (Sáiz et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Depression is accompanied by elevated levels of cytokines, and immunotherapy with IL-2 or IFN-α precipitates depression that can be attenuated with antidepressant treatment [66,67]. Higher levels of cerebrospinal fluid IL-6 have been associated with violent suicide attempts [68], with mixed findings regarding associations between other cytokine genes and suicidal behavior [69,70]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our results (concerning rs539689), they found that A allele of the -G308A polymorphism in TNF-α gene increased the susceptibility for schizophrenia only in males. Additionally TNF-α-308G/G genotype has been increased in males with suicide behavior versus control group (Omrani et al 2009), but schizophrenic patients were not included into this study.…”
Section: Discussionmentioning
confidence: 99%